Photography and Nostalgia. About the "Cold War" Film by Paweł Pawlikowski - Tomczyk-Jarzyna, Izabela (Załącznik Kulturoznawczy, 2024)
The text attempts to answer the question: why does blurring the lines between film and photography play such a significant role in Pawlikowski's movie, and how does the use of photographic solutions in the cinematic narrative lead Pawlikowski towards nostalgia. Starting from Andrei Tarkovsky’s film Mirror – which served as inspiration for Pawlikowski – and its anchoring in photography, the author tries to demonstrate that both directors utilize the inherent ability of photography to capture reality, thus making it possible to reach the image of the given memory. Furthermore, the use of photographic solutions in the film results in simplification, which, in Pawlikowski's perspective, constitutes a sign of nostalgia.